Assessing the microclimate of green and less-green tropical landscape environment - Abu Bakar, Aniza; Abdul Malek, Nurhayati (WSEAS Press, 2015)
Landscape settings shape the microclimate or thermal performance of the outdoor environment with vegetation and ground surface materials as among the affecting variables. This paper presents the microclimatic impact of landscape settings of two sites with different landscape environment during the wet and dry monsoon seasons of the tropical environment of Malaysia. The study involves field measurement of air temperature, relative humidity and wind environment from 0800hr to 1700hr, conducted on several days of the said monsoon regimes. The results show significant results in terms of the magnitude of air temperature differences between the studied sites, with similar patterns observed on the relative humidity. The wind environment seems to be also affected by the landscape settings.